T5 Oral dietary nitrate supplementation to enhance pulmonary rehabilitation in chronic obstructive pulmonary disease: a multi-centre, double blind, placebo-controlled, parallel group study. (December 2018) - Pavitt, MJ; Tanner, RJ; Lewis, AP; Buttery, SC; Mehta, B; Jefford, H; Curtis, KJ; Banya, W; Husain, S; Satkunam, K; Shrikrishna, D; D-C Man, W; et al.
Abstract : Introduction: Nitrate supplementation has been shown to augment exercise training through mechanisms including improved skeletal muscle blood flow (Ferguson et al, 2013) and efficiency of energy metabolism (Larsen et al, 2011). For individuals with COPD, dyspnoea during daily activities is a frequent occurrence with exercise training through pulmonary rehabilitation (PR) a well-established and effective therapy to ameliorate this (Rochester et al, 2015). Dietary nitrate supplementation has been shown to reduce the oxygen cost of exercise in COPD (Curtis et al, 2015). Interventions that reduce the oxygen cost of exercise and improve the response to rehabilitation may improve functional outcomes. Objectives: To investigate the hypothesis that dietary nitrate supplementation would enhance the effects of pulmonary rehabilitation in stable COPD. Methods: In a multi-centre, double blind, placebo-controlled trial (ISRCTN27860457 ) we compared the effect of 140 mls nitrate-rich beetroot juice (BR, containing 12.9 mmol nitrate) to matched placebo (PL), nitrate-deplete beetroot juice, consumed 3 hours before attending each PR session. The PR programme consisted of a twice weekly supervised strength and endurance training as well as a program of home exercises lasting 8 weeks. The primary outcome was change in incremental shuttle walk test (ISWT) distance and analysis was by intention to treat. Results presented as median (range), unless otherwise stated. Results: 166 COPD patients were recruited of whom 122 successfully completed the study (age 67.6±9.5 years, BMI 27.3±5.9 kg/m 2, FEV1 percent predicted 49.3%±17.4%, ISWT distance 286.7±151.6 m [mean ±SD]). The improvement in ISWT distance was significantly greater following nitrate supplementation 60.3 m (−110.0, 180.0) vs 30.0 m (−70.0, 290.0) for placebo, p=0.011). There was no difference in change in Quality of Life scores between groups. Both groups, had a statistically significant improvement in the mean scores for the CAT, HAD A, HAD D and MRC dyspnea scores following PR. There were no significant differences in step count or physical activity level between groups following PR. Conclusions: Dietary nitrate supplementation in association with pulmonary rehabilitation can enhance the gains in exercise capacity in COPD patients.